The Influence Of Individual Characteristics And Job Characteristics On The Performance Of Pt Surya Bumi Sentosa Employees - Hendri Dunan; Fauzan Fahlevi (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to determine the influence of individual characteristics and job characteristics on employee performance at PT. Surya Bumi Sentosa. The population of this research is employees at PT. Surya Bumi Sentosa, numbering 40 people. Total employee population of PT. Surya Bumi Sentosa has 40 employees. In this research, the entire population will be used as a sample. Therefore, the sample selection method used was the saturated sampling method. The analysis technique used in this research is quantitative data analysis which will test and analyze the data with calculations and will draw conclusions from the test results. To make it easier for researchers to carry out research, researchers carry out analysis using the SPSS 25 program with multiple linear test analysis tools, coefficient of determination test, t test and F test. The research results obtained are that individual characteristics and job characteristics both partially and anova have a positive and significant effect on employee performance at PT. Surya Bumi Sentosa.